Modeling the determinants of fertility among women of childbearing age in Nigeria: Analysis using generalized linear modeling approach (2012)
Apart from proximate determinants, certain sociodemographic factors have been reported to inform fertility in some developing nations but a comprehensive report for Nigeria is lacking in the literature. This study tested effects of some determinants of fertility on the level of fertility in Nigeria using data from the 2008 Nigerian Demographic Health Survey (NDHS). Data on 20,974 women were extracted from the 2008 NDHS data and analyzed using descriptive statistics and Poisson regression. Women with no education and those with secondary school education had 1.36 times risk and 17% increases in fertility (respectively) over those with higher education. Rural women were 1.02 times more likely to be at risk of high fertility compared to women in urban areas. Fertility level in Nigeria is higher in the rural areas than in the urban areas while level of education of women negatively impacted on their risk of having high fertility.